ANALISIS KEBUTUHAN PEMBELAJARAN SEBAGAI DASAR PERANCANGAN MODEL FLIPPED CLASSROOM BERBASIS MULTIMODAL PADA PEMBELAJARAN MENULIS TEKS EKSPLANASI - Astri Asmayanti; Elvan Yudianda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT The teaching of explanatory text writing continues to face various challenges related to both students' writing abilities and instructional design. Therefore, this study aimed to analyze instructional needs as the foundation for designing a multimodal-based flipped classroom model for teaching explanatory text writing. The study employed a qualitative descriptive approach supported by descriptive quantitative data. Data were collected through semi-structured interviews, needs analysis questionnaires, and document analysis involving three Indonesian language teachers and 36 senior high school students from three public schools in Bandung Regency, Indonesia. Qualitative data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while questionnaire data were analyzed using descriptive statistics in the form of percentages. The findings revealed that although teachers had implemented various student-centered learning models, students still experienced difficulties in generating ideas, organizing explanatory texts systematically, and comprehending learning materials. In addition, teachers had limited familiarity with the flipped classroom model and multimodal learning, whereas students demonstrated strong preferences for digital learning resources, particularly instructional videos. The instructional needs analysis further indicated that the design of the learning model should provide structured pre-class learning activities, integrate multimodal learning resources, and optimize classroom interactions through collaborative writing and feedback. These findings suggest that instructional needs analysis serves not only as an initial stage of instructional design but also as an empirical basis for determining instructional strategies, learning activities, and media selection. Consequently, the proposed multimodal-based flipped classroom model is expected to better accommodate the characteristics and learning needs of teachers and students in explanatory text writing instruction. Keywords: instructional needs analysis, flipped classroom, multimodal learning ABSTRAK Pembelajaran menulis teks eksplanasi masih menghadapi berbagai kendala, baik yang berkaitan dengan kemampuan peserta didik maupun desain pembelajaran yang digunakan guru. Oleh karena itu, penelitian ini bertujuan menganalisis kebutuhan pembelajaran (instructional needs analysis) sebagai dasar dalam perancangan model flipped classroom berbasis multimodal pada pembelajaran menulis teks eksplanasi. Penelitian menggunakan pendekatan deskriptif kualitatif dengan dukungan data kuantitatif deskriptif. Data dikumpulkan melalui wawancara semiterstruktur, angket analisis kebutuhan, dan studi dokumentasi yang melibatkan tiga guru Bahasa Indonesia serta 36 peserta didik dari tiga sekolah menengah atas di Kabupaten Bandung. Data dianalisis menggunakan model analisis interaktif Miles, Huberman, dan Saldaña, sedangkan data angket dianalisis secara deskriptif menggunakan persentase. Hasil penelitian menunjukkan bahwa guru telah menerapkan berbagai model pembelajaran yang berpusat pada peserta didik, namun peserta didik masih mengalami kesulitan dalam mengembangkan ide, menyusun struktur teks, serta memahami materi secara mendalam. Selain itu, guru belum mengenal model flipped classroom dan pembelajaran berbasis multimodal, sementara peserta didik menunjukkan preferensi terhadap penggunaan media digital, khususnya video pembelajaran. Hasil analisis kebutuhan tersebut menjadi dasar dalam menentukan sintaks, aktivitas pembelajaran, serta pemilihan media pada model flipped classroom berbasis multimodal yang dirancang. Penelitian ini menegaskan bahwa analisis kebutuhan merupakan landasan penting dalam pengambilan keputusan desain pembelajaran sehingga model yang dihasilkan lebih kontekstual, adaptif, dan sesuai dengan kebutuhan guru serta peserta didik. Kata Kunci: analisis kebutuhan pembelajaran, flipped classroom, pembelajaran multimodal